Diagnóstico para tomada de decisão na gestão de tecnologias em propriedades rurais - Pereira, Karine Vargas (2024)
There are many challenges facing agriculture and in a context in which the decision-making process is considered complex, it should be emphasized that structural changes are necessary in order to adapt to the increasingly demanding market, thus highlighting the need for new forms of management. Given this context, it is clear that Brazil needs to keep up with the global trends of the new economy and world order, but there are many challenges facing rural producers. In this sense, considering the importance of studying important factors in the management of rural organizations, the question arises: how can we systematize the various aspects that have an impact on decision-making in the management of rural properties? The general aim of the study is to propose a diagnostic model to help rural producers make decisions in the management of rural properties. The work was based on bibliographical research, with the support of a systematic literature review, considering existing documents on the subject. The research is classified as applied, with a deductive method and a qualitative approach to the problem. In terms of objectives, this is an exploratory study, using bibliographical research, data collection, documentary analysis and the content analysis technique as technical procedures. In the first stage, the work was based on a systematic literature review, focusing on studies on decision-making, digitalization and technology in agribusiness. The data search was restricted to the most respected databases, Scopus and Web of Science. The results identified five criteria and fourteen factors that influence rural producers' decision-making, which were classified into three dimensions: technology, learning and the market. Through survey instruments applied to specialists in the field, it was found that these criteria and factors are important for managing the activities of rural producers. As a contribution, we highlight the theoretical measurement model proposed, which offers a support structure for decision-making and can guide producers in understanding the information that affects the performance of their activities. The strengthening of the literature and the perceptions of experts and producers provide a significant practical contribution to the topics covered. In addition to adding value to the line of research in Production Management, the results serve as indicators in identifying and paying attention to these criteria and factors that impact decision-making in agribusiness.